The role of thrombocytapheresis in the contemporary management of hyperthrombocytosis in myeloproliferative neoplasms: A case-based review. (July 2017) - Boddu, Prajwal; Falchi, Lorenzo; Hosing, Chitra; Newberry, Kate; Bose, Prithviraj; Verstovsek, Srdan
Highlights: Pheresis use should be based upon degree of thrombocytosis and patient's risk profile. Current AFSA guidelines on plateletpheresis are not supported by randomized trials. Pheresis is favored in extreme thrombocytosis complicated by thrombohemorrhagic event. One may consider prophylactic use in settings where rapid count reduction is required. Abstract: Extreme thrombocytosis induces an acquired thrombotic-hemorrhagic diathesis, and left uncontrolled is a harbinger of potentially fatal vascular complications. Currently, cytoreduction with medical therapy remains the mainstay of hyperthrombocytosis management. However, it offers a less-than-ideal option in situations where a rapid reduction in platelets is urgently needed, as in the presence of vital end-organ ischemia or to ameliorate of life-threatening hemorrhage. The role of thrombocytapheresis, or plateletpheresis, in hyperthrombocytosis has become increasingly obsolete given the proactive titration of cytoreductive therapies and early identification and correction of reversible causes of reactive thrombocytosis. Despite its narrowed indications, plateletpheresis continues to offer a valuable temporizing measure in platelet count reduction before cytoreductive agents exert their maximal effect. In this context, it is important for the treating physician to be aware of the symptoms and risks associated with hyperthrombocytosis to inform best clinical practices. In this review, we discuss the role of plateletpheresis in the modern-day management of hyperthrombocytosis in patients with myeloproliferative neoplasms through a case based review of the literature. It becomes apparent throughout the discussion that the decision to perform plateletpheresis should be individualized based upon the clinical scenario, degree of thrombocytosis, available infrastructure and every patient's risk profile.